n Biochemiese ondersoek na voosheid by peregrine-perskes (Prunus Persica) - Von Mollendorff, Leon Johann (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc.) -- Universiteit van Stellenbosch, 1983.